THE ROLE OF FEEDBACK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the concept of feedback, its types, and its crucial role in various areas such as education, communication, and business. Feedback acts as a key mechanism for learning, improvement, and motivation, helping individuals and organizations achieve their goals more effectively. The study also examines best practices for providing feedback, the challenges involved, and strategies for delivering feedback that promotes positive outcomes.